LINGUISTIC ANALYSIS OF SELF-REPRESENTATION AND PERSONAL BRANDING ON ONLINE DATING APPLICATIONS: A CASE STUDY OF TINDER - Safira, Angelita Nanda; Sudarwati, Emy (Faculty of Administrative Science, Universitas Brawijaya, 2025)
The purpose of this study is to examine how, in the digital setting of online dating, Tinder users create their personal brands and self-representations using linguistic and multimodal strategies. This study examines how language functions as a tool for the performance of identity, social position, and symbolic capital in digital spaces. This is based on Goffman's (1959) Theory of Self-Presentation, which serves as a broad theory. This is further supported by Personal Brand Theory and Bourdieu's concepts of Cultural and Linguistic Capital. The study uses a qualitative approach with Critical Discourse Analysis (Fairclough, 2013) and includes semi-structured interviews with 15 participants aged 20 to 35, as well as textual and discourse analysis of Tinder bios and chat excerpts. The three-dimensional CDA framework developed by Fairclough is used in the analysis to examine sociocultural context, discursive practices, and textual features. The study found that Tinder users frequently employ concise, lighthearted, and casual language patterns as a tactic for self-image and attraction. While multimodal elements such as emojis, capitalization, and punctuation styles serve as visual extensions of self-expression, their educational and sociocultural backgrounds influence their linguistic creativity and tone. These linguistic performances demonstrate the negotiation of identity and symbolic hierarchies influenced by digital norms and culture. According to the study's findings, Tinder bios serve as performative platforms where users strategically employ language and multimodality to achieve a balance between cultural identity, attraction, and authenticity.